Pewarisan Ketahanan Penyakit Tungro pada Galur Padi OBSTG02-28 - Muliadi, Ahmad; Nasrullah, Nasrullah; Sumardiyono, Y. B.; Trisyono, Y. Andi (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2011)
Tungro is the most important viral disease of rice plant, caused by two types of viruses, namely Rice Tungro Bacilliform Virus (RTBV) and Rice Tungro Spherical Virus (RTSV), transmitted by green leafhopper Nephotettix virescens. Planting resistant varieties proved effective in preventing the occurrence of tungro disease explosion, but the availability of tungro virus resistant varieties are still limited. To determine the best breeding strategy, genetic inheritance model for resistance to tungro disease needs to be studied especially the gene action and the number of genes controlling resistance. For this study, variety TN1 was crossed with OBSTG02-28 to produce F1, F1R, BC1-1, BC1-2, and F2. All crosses were inoculated with tungro virus and visual symptoms of the disease were observed, followed with the ELISA test. Scoring of the disease and ELISA test showed that the resistance of OBSTG02-28 was controlled by two complementary genes with a ratio of 9:7. The additive-dominant of gene action model fitted for the inheritance of resistant gene with additive gene action. The narrow sense heritability was considered high; therefore, selection for gene resistance to tungro disease could be conducted in the early generations.